Kaposiâs Sarcoma Not Related To HIV: Case Report - Borjas, E J; Chinchilla, C E; Bejarano, S A (Journal of Medical Biomedical and Applied Sciences, 2018)
Introduction: KaposiÃ¢â¬â¢s sarcoma is an angio proliferative disorder related to a malignant neoplasm predominantly of mucocutaneous tissues. There are four clinical presentations of KaposiÃ¢â¬â¢s sarcoma: Classic, Endemic, Epidemic or related to HIV and Iatrogenic, all of which are mainly caused by human herpes virus type 8. Ã¢â¬Â©Objective: We present a case of a 73-year-old male, type II diabetic, with a family history of cutaneous carcinoma, diagnosed with non-HIV related KaposiÃ¢â¬â¢s sarcoma.Discussion: KaposiÃ¢â¬â¢s sarcoma is mainly associated with the herpes virus 8, this seems to be necessary for the development of the disease. We present a case of classical KaposiÃ¢â¬â¢s sarcoma, commonly affecting people older than 60 years. It is characterized by violaceous red maculae in lower limbs progressing to nodules. The health care provider must be able to make the diagnosis based on skin lesions and perform a biopsy only to confirm histological diagnosis. The 5-year survival for low eruptivity 97%, moderate 92.7% and high 75%.Conclusion: We found a classic Kaposi sarcoma with no relationship to HIV infection, a case not well documented, with palliative management and with a good response to it, since there are not established management protocols available.